Utilization of a Smartphone Platform for Electronic Informed Consent in Acute Stroke Trials. Issue 11 (November 2017) - Haussen, Diogo C.; Doppelheuer, Shannon; Schindler, Kiva; Grossberg, Jonathan A.; Bouslama, Mehdi; Schultz, Meagan; Perez, Hilarie; Hall, Alex; Frankel, Michael; Nogueira, Raul G.
Abstract : Background and Purpose—: The informed consent process is a major limitation for enrollment in acute stroke clinical investigations. We aim to describe the novel application of smartphone electronic informed consenting (e-Consent) in trials of cerebral thrombectomy. Methods—: The e-Consent tool consists of a secure/Health Insurance Portability and Accountability Act compliant smartphone platform based on REDCap (Research Electronic Data Capture; Vanderbilt University, TN) that uses a survey project located on a static webpage. A link to the webpage is sent via text message or email to the legally authorized representative. The e-Consent form is filled and a freehand electronic signature added in the smartphone browser; a record ID and an e-Consent Process Attestation form are automatically generated. The e-Consent application was piloted in a randomized trial comparing endovascular versus medical therapy in late presenting patients (DAWN [Clinical Mismatch in the Triage of Wake Up and Late Presenting Strokes Undergoing Neurointervention With Trevo]). Trial enrollment began in January 2015; e-Consent was approved by the local institutional review board in December 2016, and the study was stopped in February 2017. Results—: During the trial period, Grady Memorial Hospital performed 273 thrombectomies with 47 patients being consented and 38 patients enrolled in the DAWN trial. Of the randomized patients, 29 (76%) were transferred from outside hospitals. A total of 6 surrogates were e-Consented, with 2 patients being screen failures. Enrolled e-Consented patients (n=4) had similar age (73±14 versus 69±12 years; P =0.65) and National Institutes of Health Stroke Scale (16±5 versus 16±5; P =0.88) as compared with conventionally consented (n=25). Time from door-to-randomization was decreased with e-Consenting (28±9 versus 57±24 minutes; P =0.002). Conclusions—: e-Consenting streamlined the consenting process in a randomized trial of patients with emergent large vessel occlusion strokes. Abstract : Supplemental Digital Content is available in the text.